Literature Review: Impact of the Double Burden Malnutrition - Putri, Yunindah Pradita (Universitas Ibn Khaldun Bogor, 2024)
Double burden of nutrition is a nutritional problem where undernutrition and overnutrition occur together. It might happen at the level of the individual, the household, and the population. This article’s goal is to acertain how double burden of nutrition affects health, economy, and productivity. The literature review approach was used to construct this paper, results were sourced from the Google Scholar database and then selected and examined more deeply the findings. The findings of this literature review highlight the effects of the health aspect which include the emergence of infectious, chronic diseases, and cognitive impairment; the economic aspect which leads in poverty and difficulty in finding employment opportunities; and the aspect of the country's productivity will decrease.